Genetic Background of Immune Complications after Allogeneic Hematopoietic Stem Cell Transplantation in Children - Szymon Skoczen; Miroslaw Bik-Multanowski; Jacek J. Pietrzyk; Agnieszka Grabowska; Kamil Fijorek; Wojciech Strojny; Kinga Klus-Kwiecinska; Walentyna Balwierz; Maciej Siedlar (Stem Cells International)
Immune reactions are among the most serious complications observed after hematopoietic stem cell transplantation (HSCT) in children. Microarray technique allows for simultaneous assessment of expression of nearly all human genes. The objective of the study was to compare the whole genome expression in children before and after HSCT. A total of 33 children referred for HSCT were enrolled in the study. In 70% of the patients HSCT was performed for the treatment of neoplasms. Blood samples were obtained before HSCT and six months after the procedure. Subsequently, the whole genome expression was assessed in leukocytes using GeneChip Human Gene 1.0 ST microarray. The analysis of genomic profiles before and after HSCT revealed altered expression of 124 genes. Pathway enrichment analysis revealed upregulation of five pathways after HSCT: allograft rejection, graft-versus-host disease, type I diabetes mellitus, autoimmune thyroid disease, and viral myocarditis. The activation of those pathways seems to be related to immune reactions commonly observed after HSCT. Our results contribute to better understanding of the genomic background of the immunologic complications of HSCT.